The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2016
DOI: 10.1002/hep.28347
|View full text |Cite
|
Sign up to set email alerts
|

The neuroimmune guidance cue netrin‐1 controls resolution programs and promotes liver regeneration

Abstract: Hepatic ischemia/reperfusion (I/R) is a major adverse reaction to liver transplantation, hemorrhagic shock, or resection. Recently, the anti-inflammatory properties of the axonal guidance cue netrin-1 were reported. Here, we demonstrate that netrin-1 also impacts the resolution of inflammation and promotes hepatic repair and regeneration during liver I/R injury. In initial studies, we investigated the induction of netrin-1 and its receptors in murine liver tissues after I/R injury. Hepatic I/R injury was perfo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
73
0
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
3

Relationship

2
6

Authors

Journals

citations
Cited by 59 publications
(83 citation statements)
references
References 49 publications
7
73
0
1
Order By: Relevance
“…As a result, patients suffer from disruption of blood‐brain barrier (BBB), brain oedema, worsening of cognitive functions, etc . Our study is preceded by a number of reports on treatment with exogenous NTN‐1, which can efficiently alleviate inflammation in non‐neural diseases . Our data consolidated that the effects of NTN‐1 treatment in SAH‐induced early brain injury are beneficial, evidenced by reduced brain oedema and improved neurological score.…”
Section: Discussionsupporting
confidence: 55%
“…As a result, patients suffer from disruption of blood‐brain barrier (BBB), brain oedema, worsening of cognitive functions, etc . Our study is preceded by a number of reports on treatment with exogenous NTN‐1, which can efficiently alleviate inflammation in non‐neural diseases . Our data consolidated that the effects of NTN‐1 treatment in SAH‐induced early brain injury are beneficial, evidenced by reduced brain oedema and improved neurological score.…”
Section: Discussionsupporting
confidence: 55%
“…Similarly, severe liver damage can be confirmed on the clinical symptoms of hepatic ischemia/reperfusion, hemorrhagic shock, or resection, decreasing pro-inflammatory mediators, increasing efferocytosis of apoptotic PMNs, endogenous biosynthesis of SPMs and the generation of specific growth factors [156]. Chronic liver disease (CLD) can also be confirmed by decreased thrombopoietin production and accelerated platelet destruction caused by hypersplenism [157]. In case of hepatocellular carcinoma REILD FGF-19 and HGF seems to be important therapeutic markers [158,159].…”
Section: Therapeutic Role Of Cell Secreted Growth Factorsmentioning
confidence: 97%
“…As a result, netrin-1 significantly shortens the time required for resolution, which is a quantitative measure of resolution and tissue regeneration. Extension of this work showed that netrin-1 is an innate immune system resolvent that can induce tissue-specific regeneration programs and promote organ recovery [52] (Figure 2[ 4 …”
Section: Impact Of Neuronal Guidance Proteins On the Resolution Of Inmentioning
confidence: 98%
“…As mentioned above, Schlegel et al demonstrated that netrin-1 increases the regeneration capacity following hepatic IR injury. This was associated with improved liver repair via the stimulation of proresolving lipid mediators (SPMs) and the generation of hepatic growth factors [52].…”
Section: Neuronal Guidance Protein Signaling During Conditions Of Iscmentioning
confidence: 99%